Investigating brand image and brand trust in airline service: Evidence of Korean Air - Nguyen Thi Cam Le; Mai Ngoc Khuong (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: Branding is a predominant part of a marketing strategy. When the brand building is implemented effectively, it delivers customer satisfaction, nurtures customer loyalty to a higher level, and ensures greater airline success. This study explores the relationships of price, safety, and in-flight service quality with airline customers' perceptions of the brand image and trust and clarifies their impact on customer satisfaction and loyalty. Methods:A sample of 367 valid responses adopting a convenience sampling method was collected from customers of Korean Air. Data analysis was conducted using Partial Least Squares SEM method. Results:The findings connote that price, safety, and in-flight services are the core factors determining the creation of a strong impression in customers' minds about airline brands and have different impacts on customer satisfaction and loyalty. The mediating effects of brand trust and customer satisfaction on the relationship between brand image and customer loyalty were also highlighted. Implications:This study underlines that airlines should focus on controlling and maintaining the brand stance in consumer perception. Therefore, there is a need to provide a flight experience that meets consumer expectations in terms of providing a positive brand image and building brand trust in order to generate customer satisfaction and loyalty.
Keywords: L8; M3; L93; 330; brand trust; brand image; customer satisfaction; customer loyalty